The efficacy and safety of exercise and physical activity on psychosis: A systematic review and meta-analysis - Ziebart, Christina; Bobos, Pavlos; MacDermid, Joy C.; Furtado, Rochelle; Sobczak, Daniel J.; Doering, Michele (Frontiers in Psychiatry, 2022)
Background: Treatment of psychosis typically focuses on medication, but some of these medications can have unintended side effects, exercise has global health benefits, with minimal side effects. The purpose of this systematic review and meta-analysis is to investigate the effectiveness of exercise and physical activity on psychotic symptoms, in people with psychosis when compared to usual care, in a hospital setting. Methods: A systematic electronic search of the literature was performed in August 2021, in PubMed, Scopus, and PsychINFO with no date restrictions. We included randomized trials (RCTs) with patients with psychosis that received an exercise intervention within a hospital setting. The primary outcome of interest in this review was psychosis symptom severity scores and safety outcomes. Results: A total of 23 articles were included in this systematic review, with 17 included in the meta-analysis, including 1473 participants. Meta-analysis of RCTs demonstrate that exercise in hospital setting reduces psychosis symptom severity scores when compared to control or usual care with a pooled mean difference of -8.7 (95% confidence interval [CI] -13.8 to -3.6). Studies not included in the meta-analysis showed improvements in PANSS. Two studies found statistically significant improvements, but almost all studies found clinically important differences. Conclusion: Exercise can be effective in decreasing psychosis symptom severity scores in the hospital setting compared to usual care or control. Greater implementation of formal exercise programs in hospitals would benefit hospitalized patients with psychosis.